1999
DOI: 10.1111/j.1749-7345.1999.tb00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Replacement of Fish Meal with Corn Gluten Meal in Diets for Japanese Flounder Paralichthys olivaceus

Abstract: Abstract.— Feeding experiments were conducted to evaluate corn gluten meal (CGM) as an alternative protein source for fish meal in the diet of Japanese flounder Paralichthys olivaceus. A diet containing 75% white fish meal as a sole protein source was the control, and 20, 40, and 60% of fish meal protein was replaced with CGM protein in the experimental feeds. Juvenile fish of about 8 g initial body weight were fed each diet to apparent satiation twice a day. 6 d per week for 8 wk at 20 C. Survival rates of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
3
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 22 publications
8
61
3
3
Order By: Relevance
“…In contrast, Kumar et al (2010) and Akinleye et al (2012) observed increased triglyceride levels in fish fed plant protein based diets against fish meal (control), hence, the variation observed in comparison with our findings may be due to the differences in the major protein source used as control. Elevated blood glucose level has been reported in many fish species fed plant protein based diets due to the higher contents of carbohydrates, and the result obtained in the present study is in accord with other findings (Kikuchi, 1999;Kumar et al, 2010;Akinleye et al, 2012). Conversely, Slawski et al (2012) detected no significant differences in the plasma glucose levels in rainbow trout fed rapeseed protein concentrate.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, Kumar et al (2010) and Akinleye et al (2012) observed increased triglyceride levels in fish fed plant protein based diets against fish meal (control), hence, the variation observed in comparison with our findings may be due to the differences in the major protein source used as control. Elevated blood glucose level has been reported in many fish species fed plant protein based diets due to the higher contents of carbohydrates, and the result obtained in the present study is in accord with other findings (Kikuchi, 1999;Kumar et al, 2010;Akinleye et al, 2012). Conversely, Slawski et al (2012) detected no significant differences in the plasma glucose levels in rainbow trout fed rapeseed protein concentrate.…”
Section: Discussionsupporting
confidence: 91%
“…tenellum, there are some studies on physiology (Signoret et al, 1997;Hernandez et al, 1995;1996), biology (Román-Contreras, 1979) and reproduction (Rodríguez-González, 1998), but information about nutrition is scarce. Since plant protein meals are cheaper than animal protein sources, much research has been focused in substituting animal protein with the plant protein meals (Akiyama, 1988;Kikuchi, 1999). However, it has been proved that the dietary inclusion of plant protein meal, generally reduce growth and feed efficiency in fish and shellfish species (Cowey et al, 1971;Akiyama et al, 1989).…”
Section: Mean Body Length (Cm)mentioning
confidence: 99%
“…SP and CG are ingredients that have been previously used to replace FM in aquaculture diets for crustaceans and fish. Most studies indicate that better results in terms of biomass production, survival and hematological parameters are achieved when these ingredients have been used at low to medium replacement levels and in conjunction with other ingredients derived from plant or animal sources (Kikuchi, 1999;Lewis and Kohler, 2008;Li et al, 2012;Regost et al, 1999;Robaina et al, 1997;Sookying and Davis, 2012;Ye et al, 2011). However, successful substitution of high levels of dietary FM using plant proteins has also been reported for some marine organisms.…”
Section: Dietmentioning
confidence: 99%